Positive electrode material and preparation method thereof, positive electrode plate and secondary battery
By controlling the aspect ratio and micropowder content of particles in the positive electrode material, the shortcomings of existing positive electrode materials in high-temperature storage performance and energy density are solved, and the comprehensive performance of the material is improved.
Patent Information
- Application Number
- CN202411934832.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The existing ternary cathode materials have poor high-temperature storage performance and low energy density, which require improvement.
By controlling the average length-to-diameter ratio X/Y of the particles in the positive electrode material within the range of 1≤X/Y≤1.6, and after compacting under 6T pressure, it is ensured that the volume of particles below 1μm accounts for 2%~4%. To improve the circulation performance of materials and high temperature storage performance.
The long-term circulation performance and high-temperature storage performance of the positive electrode material are improved, while ensuring the good capacity of the material and improving the overall performance.
Smart Images

Figure CN119481035A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of battery positive electrode materials, and in particular to a positive electrode material and a preparation method thereof, a positive electrode sheet and a secondary battery. Background Art
[0002] Ternary cathode material is one of the most widely used cathode materials in lithium-ion batteries. It has the advantages of high discharge specific capacity and high energy density, and its production cost is much lower than that of LiCoO 2 Among the many cathode materials, ternary cathode materials have become the most widely used cathode materials in the field of lithium-ion batteries due to their advantages of high specific capacity and high voltage platform. However, the existing cathode materials have poor high-temperature storage performance and low energy density, which are in urgent need of improvement. Summary of the invention
[0003] In view of this, in order to solve at least one of the above defects, it is necessary to provide a positive electrode material.
[0004] In addition, it is also necessary to provide a method for preparing the aforementioned positive electrode material, and a positive electrode sheet and a secondary battery using the aforementioned positive electrode material.
[0005] In a first aspect, an embodiment of the present application provides a positive electrode material, wherein an average aspect ratio X / Y of particles in the positive electrode material satisfies: 1≤X / Y≤1.6, wherein X is the length of the longest straight side of a single particle, and Y is the length of a straight side perpendicular to the midpoint of the longest straight side; after compaction under a pressure of 6T, the volume proportion of particles below 1 μm in the positive electrode material is 2%~4%.
[0006] In some possible embodiments, in the positive electrode material, after compaction at a pressure of 6T, particles with a size of 0 to 1 μm in the positive electrode material account for 10% to 20% of the volume fraction of particles with a size of 0 to 2 μm.
[0007] In some possible embodiments, the number of particles in the positive electrode material that satisfy 1≤X / Y≤1.6 accounts for no less than 90%.
[0008] In some possible embodiments, the general formula of the positive electrode material is as follows: Li x Ni a Co b N c M d O 2, M is an added element, N element includes at least one of Al and Mn, M element includes at least one of Al, Ti, Zr, Mg, Sr, Ba, B, Ca, Nb, W, Sb, Ta, Sn and Y, wherein 0.98≤x≤1.1, 0.50≤a≤0.98, 0<b≤0.20, 0<c≤0.35, 0≤d≤0.10, a+b+c+d=1.
[0009] In some possible embodiments, the positive electrode material is a single crystal positive electrode material, and an average particle size of particles in the positive electrode material is 1 μm to 5 μm.
[0010] In some possible embodiments, the median particle size D of the positive electrode material V 50 is 2μm~6μm.
[0011] In some possible embodiments, (D90-D10) / D50 of the positive electrode material is ≤2.
[0012] In some possible embodiments, the specific surface area of the positive electrode material is 0.4 m 2 / g ~0.8 m 2 / g.
[0013] In some possible embodiments, the compaction density of the positive electrode material is ≥3.0 g / cm 3 .
[0014] In some possible embodiments, the tap density of the positive electrode material is ≥1.5 g / cc.
[0015] In some possible embodiments, the pH of the positive electrode material is ≤12.
[0016] The present application also provides a method for preparing a positive electrode material, comprising the following steps: mixing a precursor with a first additive to form a mixture, and pre-sintering the mixture to obtain a pre-sintered product; sintering the pre-sintered product once to obtain a positive electrode material matrix; crushing the positive electrode material matrix, wherein the aspect ratio of particles in the crushed positive electrode material matrix satisfies: 1≤X / Y≤1.6, wherein X is the length of the longest straight side of a single particle, and Y is the length of a straight side perpendicular to the midpoint of the longest straight side; after compaction under a pressure of 6T, the volume proportion of particles below 1 μm in the positive electrode material matrix is in the range of 2% to 4%; and mixing the crushed positive electrode material matrix with a second additive and performing a secondary sintering to obtain the positive electrode material.
[0017] In some possible embodiments, in the step of mixing the precursor with the first additive to form a mixture, the mixture also includes a pore former, and the added amount of the pore former accounts for 3% to 10% of the mass of the positive electrode material precursor.
[0018] In some possible embodiments, the primary sintering includes a first sintering stage and N second sintering stages performed sequentially, wherein the temperature of each of the second sintering stages is lower than the temperature of the first sintering stage, and the temperature gradient of the N second sintering stages decreases, and N is an integer greater than or equal to 1.
[0019] In some possible embodiments, the pre-sintering temperature T1 is 500-900° C., and the time is 2-8 hours.
[0020] In some possible embodiments, the temperature T2 of the first sintering stage is 800~1000℃, and the time is 2~6h; the temperature of each second sintering stage is T2-n*ΔT, and the time is 2~6h, where n is the order of the second sintering stage in N second sintering stages, n is an integer greater than or equal to 1, ΔT is 20~40℃, and the total duration of the sintering once does not exceed 16 hours.
[0021] In some possible embodiments, the cathode material precursor is of the general formula Ni a Co b N c (OH) 2 , wherein the N element is selected from at least one of Mn and Al, a+b+c=1, 0.50≤a≤0.98, 0<b≤0.20, 0≤c≤1-ab.
[0022] In some possible embodiments, the first additive includes at least one of lithium salts, compounds of Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn and Y, and the first additive contains at least lithium salts.
[0023] In some possible embodiments, the second additive includes at least one of compounds of B, Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn and Y.
[0024] In a third aspect, an embodiment of the present application provides a positive electrode plate, comprising a positive electrode collector and a positive electrode active material layer disposed on at least one surface of the positive electrode collector, wherein the positive electrode active material layer comprises the positive electrode material as described above or a positive electrode material prepared by the method for preparing the positive electrode material as described above.
[0025] In a fourth aspect, an embodiment of the present application provides a secondary battery, comprising the positive electrode material as described above or the positive electrode material prepared by the method for preparing the positive electrode material as described above.
[0026] The positive electrode material and preparation method thereof provided in the embodiments of the present application control the aspect ratio of the particles in the positive electrode material and the volume proportion of particles below 1 μm in the positive electrode material, so as to improve the long-term cycle performance, high-temperature storage performance and gas production performance of the positive electrode material while ensuring that the material has good capacity, thereby achieving an improvement in the comprehensive performance of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a schematic cross-sectional view of a lithium-ion battery using the positive electrode material of an embodiment of the present application during charging.
[0028] Figure 2 It is a schematic cross-sectional view of a lithium-ion battery using the positive electrode material of an embodiment of the present application during discharge.
[0029] Figure 3 This is a scanning electron microscope (SEM) photograph of the positive electrode material of Example 1 of the present application.
[0030] Figure 4 This is a scanning electron microscope (SEM) photograph of the positive electrode material of Comparative Example 1.
[0031] Figure 5 This is a cycle comparison diagram of Example 1 of the present application and Comparative Examples 1-2. DETAILED DESCRIPTION
[0032] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application; it should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by technicians in the technical field of the present application; in the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other; many specific details are elaborated in the following description to facilitate a full understanding of the present application, and the described embodiments are only part of the embodiments of the present application, not all of the embodiments.
[0033] An embodiment of the present application provides a positive electrode material, in which the average aspect ratio X / Y of particles satisfies: 1≤X / Y≤1.6, wherein X is the length of the longest straight side of a single particle, and Y is the length of a straight side perpendicular to the midpoint of the longest straight side; after compaction under a pressure of 6T, the volume proportion of particles below 1 μm in the positive electrode material is 2%~4%.
[0034] First, this application controls the average aspect ratio X / Y of the particles in the positive electrode material to satisfy 1≤X / Y≤1.6. The aspect ratio of the particles within this range is relatively low, and the particles with low aspect ratio have high roundness. The improved roundness is conducive to reducing the specific surface area of the positive electrode material, and the smaller specific surface area is conducive to reducing the direct contact between the positive electrode material and the electrolyte, thereby reducing the generation of side reactions, and is conducive to improving the long-term cycle performance, high-temperature storage performance and gas production performance of the positive electrode material. This application further controls the positive electrode material to be compacted under a pressure of 6T, and the volume proportion of particles below 1μm in the positive electrode material is in the range of 2%~4%. By controlling the volume proportion of particles below 1μm (defined as micropowder) of the positive electrode material to be within the above range, the side reactions between the positive electrode material and the electrolyte can be reduced during the charge and discharge process of the battery, and the gas production can be reduced, thereby further improving the cycle life and high-temperature storage performance of the positive electrode material.
[0035] Secondly, by regulating the particles below 1um within the above range, the micropowder in the material can fill the gaps between large particles during the preparation of the pole piece, thereby increasing the compaction density of the material and improving the problem of reduced capacity caused by the aspect ratio of the particles in the range of 1 to 1.6, which causes the number of micropowders in the material to decrease, the particle size distribution of the material to narrow, and the compaction density of the material to decrease. Therefore, a higher volume energy density can be obtained without causing the specific surface area to lose control and increase side reactions.
[0036] For example, the average aspect ratio X / Y of the particles can be 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, or any value within the range formed by any two of the above values. The volume proportion of particles below 1 μm in the positive electrode material can be 2%, 2.5%, 3%, 3.5%, 4%, or any value within the range formed by any two of the above values.
[0037] Particles of 0~1μm account for 10%~20% of the volume fraction of particles of 0~2μm. By further regulating the volume fraction of particles of 0~1μm to 0~2μm within the above range, the compaction density of the material can be further improved, and the problem of the reduction of the number of small particles and fine powders of the material caused by the aspect ratio of the particles in the range of 1~1.6, the narrowing of the particle size distribution of the material, and the reduction of the compaction density of the material, thereby reducing the capacity, can be further improved. Exemplarily, particles of 0~1μm account for 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% of the volume fraction of particles of 0~2μm, or any value within the range composed of any two of the above values. It should be noted that particles of 0~1μm are defined as micropowders and particles of 1~2μm are defined as small particles.
[0038] Therefore, the present application controls the aspect ratio of the particles, the content of micropowder in the positive electrode material, and the proportion of particles of different particle sizes, in order to improve the long-term cycle performance, high-temperature storage performance, and gas production performance of the positive electrode material while ensuring that the material has good capacity and achieving an improvement in the comprehensive performance of the positive electrode material.
[0039] In some embodiments, the number of particles in the positive electrode material that satisfy 1≤X / Y≤1.6 accounts for more than 90%. By controlling the aspect ratio of more than 90% of the particles in the material to be 1-1.6, it is beneficial to improve the roundness of the overall particles in the positive electrode material, further reduce the specific surface area of the positive electrode material, reduce the generation of side reactions, and further improve the long-term cycle performance, high temperature storage performance, and gas production performance of the positive electrode material.
[0040] In some embodiments, the specific surface area of the positive electrode material is 0.4 m 2 / g ~0.8 m 2 / g, the particles in the positive electrode material have a smaller aspect ratio, the particles are more rounded, the amount of micropowder is less, and the specific surface area is smaller. The small specific surface area is conducive to reducing the direct contact between the positive electrode material and the electrolyte, thereby reducing the generation of side reactions, and is conducive to improving the long-term cycle performance, high-temperature storage performance and gas production performance of the positive electrode material. For example, the specific surface area of the positive electrode material can be 0.4 m 2 / g, 0.5m 2 / g, 0.6 m 2 / g, 0.8 m 2 / g or any value within the range formed by any two of the above values.
[0041] In some embodiments, the positive electrode material may be a single crystal positive electrode material, and the average particle size of a single particle in the positive electrode material may be 1 μm to 5 μm. For example, the average particle size of a single particle may be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, or any value within the range formed by any two of the above values.
[0042] It should be noted that the difference between single crystal positive electrode materials and polycrystalline positive electrode materials (i.e., polycrystalline secondary particles) is that the smallest particle of polycrystalline secondary particles is a secondary particle formed by the agglomeration of nanometer-scale primary particles. For single crystal positive electrode materials, the smallest particle is usually a single primary particle of micrometer scale. Generally speaking, in addition to EBSD testing methods, characterization methods such as scanning electron microscopy (SEM) can also be used to determine whether the obtained positive electrode product is a single crystal material. For example, for single crystal positive electrode materials, the morphology of single crystal particles can be characterized by SEM, and it can be seen that the shape of single crystal particles is generally regular or irregular spherical, and there is no significant particle agglomeration. The orientation of single crystal positive electrode materials can also be characterized by EBSD. Through EBSD, it can be observed that the color in at least one grain is the same, so as to judge that the orientation in at least one grain is the same, and the grains with the same orientation are single crystals. It should be specifically noted that the "single crystal positive electrode material" known to those skilled in the art is not a "single crystal" in the strict crystallographic sense. In crystallography, an ideal single crystal refers to a crystal with completely the same arrangement and orientation. However, due to impurities, strain and crystal defects, ideal single crystals are very rare and difficult to produce in the laboratory. Therefore, the single crystal positive electrode materials known in the art are actually more "single crystal morphology" positive electrode materials, which only show a large particle size similar to a single crystal in size, which is different from a polycrystal composed of many small primary particles. For ease of understanding, the single crystal positive electrode material involved in this application can be understood as a positive electrode material particle containing a single grain with the same orientation, and the average particle size of the above single grain is 1μm~5μm.
[0043] It can be understood that a single grain in the present application can be a single particle composed of a primary particle. The above-mentioned single crystal positive electrode material may also contain a small amount of "quasi-secondary particles" formed by the adhesion of several single particles. "Primary particle" refers to the smallest particle unit identified when observing the positive electrode active material through a scanning electron microscope, and "secondary particle" refers to a secondary structure formed by the agglomeration of multiple primary particles, showing a relatively rounded spherical morphology. "Quasi-secondary particles" refer to those formed by the adhesion of several single particles. Usually, the particle size of a single particle in the above-mentioned quasi-secondary particles is usually between 1μm and 5μm. In general, the roundness of the particles of "quasi-secondary particles" is lower than that of the above-mentioned conventional "secondary particles".
[0044] It should be further explained that the "single crystal" in the "single crystal positive electrode material" known to those skilled in the art is not a "single crystal" in the strict sense. In crystallography, an ideal single crystal refers to a crystal with exactly the same arrangement and orientation. However, due to impurities, strain and crystal defects, ideal single crystals are very rare and difficult to produce in the laboratory. Therefore, the single crystal positive electrode materials known in the art are actually more of "single crystal-like morphology" positive electrode materials, which only show a large particle size similar to a single crystal in size, which is different from a polycrystal composed of many small primary particles.
[0045] In some embodiments, the median particle size D50 of the positive electrode material is 2μm~6μm. The median particle size D50 represents the particle size of the material particles corresponding to the cumulative particle size distribution percentage reaching 50% volume ratio. The present application controls the median particle size of the positive electrode material within the above appropriate range, and the particle size is moderate, which is beneficial to reduce the specific surface area of the particles and reduce the side reactions between the particles and the electrolyte, thereby improving the safety and cycle life of the material; at the same time, particles of the above range size are also beneficial to reduce the internal stress of the particles and reduce the risk of electrochemical polarization of lithium ions inside and outside the particles, thereby increasing the capacity of the positive electrode material. Exemplarily, the median particle size D50 of the positive electrode material is 2μm, 3μm, 4μm, 5μm, 6μm or any value within the range composed of any two of the above values.
[0046] In some embodiments, (D90-D10) / D50 of the positive electrode material is ≤2. D10 in the particle size distribution represents the particle size corresponding to when the cumulative particle size distribution reaches 10%, that is, in the particle group, 10% of the particles are smaller than this particle size. Usually, D10 is used to describe particles with finer particle sizes in a particle group. D90 represents the particle size corresponding to when the cumulative particle size distribution reaches 90%, that is, in the particle group, 90% of the particles are smaller than this particle size. D90 is usually used to describe particles with coarser particle sizes in a particle group. (D90-D10) / D50 represents the width of the particle size distribution in the positive electrode material. In the present application, by controlling (D90-D10) / D50≤2, the particle size distribution of the positive electrode material is moderate, which can reduce the specific surface area of the particles without reducing the compaction density of the material, thereby ensuring that the positive electrode material has excellent cycle performance, storage performance and capacity. Illustratively, (D90-D10) / D50 of the positive electrode material can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2 or any value within the range formed by any two of the above values.
[0047] In some embodiments, the powder compaction density of the positive electrode material is ≥3.0 g / cm 3 By controlling the aspect ratio of the particles in the material and adjusting the proportion of micropowder and small particles, the powder compaction density of the positive electrode material can be effectively improved, thereby ensuring that the positive electrode material has a higher compaction density when it is made into a pole piece, so as to increase the capacity of the positive electrode material. For example, the powder compaction density of the positive electrode material can be 3.0g / cm 3 、3.1g / cm 3 、3.2g / cm 3 、3.3g / cm 3 、3.4g / cm3 , 3.5g / cm 3 、3.6g / cm 3 、3.7g / cm 3 、3.8g / cm 3 、3.9g / cm 3 , 4g / cm 3 wait.
[0048] In some embodiments, the tap density of the positive electrode material is ≥1.5 g / cm 3 By adjusting the proportion of micropowder and small particles in the positive electrode material, the tap density of the positive electrode material can be effectively improved, so that the tap density of the material is 1.5 g / cm 3 The above can improve the compaction density of the electrode sheet, which is beneficial to improve the capacity of the battery. For example, the tap density of the positive electrode material can be 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3 , 2g / cm 3 , 2.1g / cm 3 , 2.2g / cm 3 , 2.3g / cm 3 , 2.4g / cm 3 , 2.5g / cm 3 wait.
[0049] In some embodiments, the pH of the positive electrode material is ≤ 12. By controlling the aspect ratio of the particles and the proportion of micropowders and small particles, it is beneficial to reduce the specific surface area of the particles while increasing the compaction density of the material. At the same time, controlling the pH value of the positive electrode material within a suitable range can effectively improve the electrochemical activity of the positive electrode material and ensure the smooth diffusion of lithium ions in the material, thereby improving the battery performance. Exemplarily, the pH of the positive electrode material can be 12, 11, 10, 9, 8, etc.
[0050] In some embodiments, the general formula of the positive electrode material is as follows: Li x Ni a Co b N c M d O 2, N element includes at least one of Mn and Al, M element includes at least one of Al, Ti, Zr, Mg, Sr, Ba, B, Ca, Nb, W, Sb, Ta, Sn and Y, wherein 0.98≤x≤1.1, 0.50≤a≤0.98, 0<b≤0.20, 0<c≤0.35, 0≤d≤0.10, a+b+c+d=1. By doping the ternary positive electrode material, the crystal structure of the positive electrode material can be optimized, the surface morphology of the particles can be further improved, and the structural stability and conductivity of the positive electrode material can be further improved.
[0051] The present application also provides a method for preparing the aforementioned positive electrode material, which specifically comprises the following steps: Step S1, adding a first additive to a mixture of a precursor and a lithium salt to mix the mixture to obtain a mixture, and pre-sintering the mixture to obtain a pre-sintered product.
[0052] The pre-sintering is carried out in an oxygen or air atmosphere to achieve a reaction between the material and oxygen to form a target layered compound.
[0053] In some embodiments, during the pre-sintering process, the pressure in the reactor is controlled within the range of 20Pa~60Pa, the pre-sintering temperature can be 500~900℃, and the sintering time can be 2~8h. Controlling the sintering furnace pressure and temperature can fully embed the lithium salt into the precursor and reduce the residual lithium salt. At the same time, during the pre-oxidation sintering process, the micropowder can undergo a certain pre-fusion, control the aspect ratio of the particles, make the particles more rounded, and reduce the micropowder on the surface of the material. Exemplarily, the pre-sintering temperature can be 500℃, 600℃, 700℃, 800℃, 900℃ or any value within the range composed of any two of the above values; the pre-sintering time can be 2h, 3h, 4h, 5h, 6h, 7h, 8h or any value within the range composed of any two of the above values.
[0054] In some embodiments, a pore former can also be added to the mixture, wherein the mass of the pore former accounts for 3% to 10% of the mass of the precursor. Since the material needs to react with oxygen to form the target layered compound during the sintering process, it is difficult for oxygen to completely penetrate the mixture. Therefore, the pore former is added during sintering. The pore former will completely decompose at high temperature without obvious residue and will not produce impurities. At the same time, the pore former decomposes to produce gas, and the gas forms pores inside the mixture when it is discharged. These pores are conducive to the infiltration of oxygen, thereby allowing the material inside the mixture to fully react, reducing lithium residues, reducing the residue of micropowder on the surface of the material, and further controlling the particle size. Exemplarily, the mass of the pore former accounts for 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% of the mass of the positive electrode material precursor or any value within the range composed of any two of the above values.
[0055] In some embodiments, the pore former may include at least one of starch, pine wood powder, polyvinyl alcohol, polyethylene glycol, coal powder, lithium peroxide, and the like.
[0056] In some embodiments, the general formula of the cathode material precursor can be Ni a Co b N c (OH) 2 or LiNi a Co b N c O 2 , where a+b+c=1; 0.5≤a≤0.98, 0≤b≤0.20, 0≤c≤1-ab. The first additive may include a lithium salt and a dopant, wherein the dopant may include at least one of compounds such as Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn and Y, wherein the lithium salt may be LiOH, Li 2 CO 3 According to the different types of positive electrode material precursors, there are certain differences in the selection of the first additive, and the first additive contains at least a lithium salt.
[0057] In some embodiments, in the pre-sintered product, the ratio of the molar amount of Li element to the total molar amount of other metal elements may be 0.98-1.10.
[0058] In some embodiments, the first additive may include TiO 2 、AlOOH、WO 3 、ZrO 2 , Y 2 O 3 、NbO 2 At least one of the above.
[0059] Step S2, sintering the pre-sintered product once to obtain a positive electrode material matrix.
[0060] The one-time sintering includes a first sintering stage and N second sintering stages performed sequentially, wherein the temperature of each second sintering stage is lower than the temperature of the first sintering stage, and the temperature gradient of the N second sintering stages decreases, and N is an integer greater than or equal to 1. In other words, the one-time sintering is a multi-gradient sintering process, including a high-temperature first sintering stage and multiple low-temperature second sintering stages, and the temperature of different second sintering stages decreases with the increase of the number of sintering times.
[0061] In some embodiments, the temperature T2 of the first sintering stage is 800-1000°C, and the time is 2-6 hours. For example, the temperature of the first sintering stage can be 800°C, 850°C, 900°C, 950°C, 1000°C, or any value in the range of any two of the above values; the sintering time can be 2h, 3h, 4h, 5h, 6h, or any value in the range of any two of the above values.
[0062] In some embodiments, the average heating rate of the first sintering stage is ≤5°C / min. For example, the heating rate may be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, or any value within a range consisting of any two of the above values.
[0063] In some embodiments, the temperature of each second sintering stage is T2-n*ΔT, and the time is 2~6h, where n is the order of the second sintering stage in the N second sintering stages, n is an integer greater than or equal to 1, and ΔT can be 20~40°C, for example, ΔT can be 20°C, 30°C, 40°C or any value in the range composed of any two of the above values.
[0064] In some embodiments, a sintering process may include three gradient sintering stages, that is, N is equal to 2. At this time, the temperature T3 of the first second sintering stage may be T2-ΔT, and the sintering time may be 2~4h. The temperature T4 of the second second sintering stage may be T2-2*ΔT, and the sintering time may be 2~6h.
[0065] In some embodiments, the total sintering time of one sintering may be 6 to 16 hours. For example, the total sintering time may be 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, or any value within the range consisting of any two of the above values.
[0066] The pressure in the reactor is 20Pa~60Pa, and the time is 2~6h at 800~1000℃. The high-temperature sintering process can make the pre-sintered product and the micro-powder initially fuse, making the particles more rounded, so as to achieve the purpose of controlling the particle aspect ratio, particle size, and the content of the micro-powder; then sintering at a temperature of T2-ΔT for 2~4h, and continuing to sinter under appropriately reduced temperature conditions, the pre-sintered product and the micro-powder can be further fused, and the particles will not grow too large due to excessive temperature, so as to further control the aspect ratio and particle size of the particles; finally, the temperature is further reduced, and sintering at a temperature of T2-2*ΔT for 2~6h, and the temperature is further reduced to achieve further fusion of the pre-sintered product and the micro-powder, and further control the aspect ratio and particle size of the particles. This step first realizes the embedding of lithium ions and the initial growth of particles through high-temperature sintering, and then performs two stages of low-temperature sintering, which can further embed lithium ions and also play the role of annealing and repairing micro-grain boundaries. By controlling the temperature and reaction time of particle fusion, the aspect ratio, particle size and micro powder content of the single crystal particles can be effectively controlled. In addition, the total sintering time of the three sintering stages does not exceed 16 hours, which can control the size of the single crystal particles within an appropriate range to prevent the crystals from growing too large.
[0067] It can be understood that step S1 and step S2 can also be combined to form multi-gradient sintering by controlling the temperature and time of different sintering stages.
[0068] Step S3, the positive electrode material matrix is crushed, and the aspect ratio of the single crystal particles in the obtained positive electrode material matrix satisfies: 1≤X / Y≤1.6, and after compaction under a pressure of 6T, the volume proportion of particles below 1μm in the positive electrode material matrix is calculated by Malvern 3000 particle size tester to be in the range of 2%~4%.
[0069] Through the pre-sintering and primary sintering processes in the aforementioned steps, the aspect ratio, particle size and powder content of the single crystal particles can be controlled, and after pulverization, a positive electrode material matrix that meets the above requirements can be obtained.
[0070] In some embodiments, particles with a size of 0-1 μm in the positive electrode material matrix account for 10%-20% of the volume fraction of particles with a size of 0-2 μm.
[0071] Step S4, mixing the crushed positive electrode material matrix with the second additive and performing secondary sintering to obtain the evidence material.
[0072] Specifically, the qualified positive electrode material matrix that meets the conditions in step S3 is subjected to secondary sintering with the second additive under an oxygen atmosphere, wherein the second additive includes at least one of compounds such as B, Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn and Y. The second additive is a coating agent, and the secondary sintering is low-temperature sintering, the purpose of which is to uniformly coat the coating agent on the surface of the positive electrode material matrix for surface modification, so as to further improve the structural stability and electrochemical properties of the positive electrode material, and has no significant effect on the particle size and aspect ratio of the positive electrode material. It can be understood that the particle size of the positive electrode material can well inherit the particle size of the matrix, and the subsequent coating process has little effect on the particle size of the matrix.
[0073] In some embodiments, the temperature of the secondary sintering can be 500-900°C, the sintering time can be 6-16h, and the average heating rate is ≤5°C / min. By controlling the temperature, time and heating rate of the secondary sintering, the second additive can be evenly coated on the surface of the substrate, further optimizing the surface structure of the positive electrode material, so as to further improve the structural stability and electrical properties of the positive electrode material. Exemplarily, the temperature of the secondary sintering can be 500°C, 600°C, 700°C, 800°C, 900°C or any value in the range of any two of the above values; the time of the secondary sintering can be 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h or any value in the range of any two of the above values.
[0074] The positive electrode material and preparation method provided in the embodiment of the present application control the aspect ratio of the particles in the positive electrode material, the content of the micropowder in the positive electrode material, and the proportion of particles of different particle sizes, in order to improve the long-term cycle performance, high-temperature storage performance, and gas production performance of the positive electrode material, while ensuring that the material has good capacity and improving the comprehensive performance of the positive electrode material. Among them, the aspect ratio X / Y of the particles is controlled to satisfy 1≤X / Y≤1.6. The aspect ratio of the particles within this range is relatively low, and the roundness of the particles with a low aspect ratio is relatively high. The improvement of the roundness is conducive to reducing the specific surface area of the positive electrode material, and the smaller specific surface area is conducive to reducing the direct contact between the positive electrode material and the electrolyte, thereby reducing the generation of side reactions, which is conducive to improving the long-term cycle performance, high-temperature storage performance, and gas production performance of the positive electrode material. In addition, by further controlling the volume proportion of particles below 1 μm in the positive electrode material to 2%~4%, on the one hand, the side reaction between the positive electrode material and the electrolyte can be reduced during the charge and discharge process of the battery, and the gas production can be reduced, thereby further improving the cycle life and high-temperature storage performance of the positive electrode material; on the other hand, in the process of preparing the electrode sheet, the fine powder in the material can fill the gaps between the large particles, thereby increasing the compaction density of the material and improving the problem of a decrease in the number of fine powders of the material caused by the average aspect ratio of the particles in the range of 1~1.6, a narrowing of the particle size distribution of the material, a decrease in the compaction density of the material, and thus a decrease in the capacity. Therefore, a higher volume energy density can be obtained without causing the specific surface area to be out of control and increase side reactions.
[0075] An embodiment of the present application also provides a positive electrode sheet using the aforementioned positive electrode material, comprising a positive electrode collector and a positive electrode active material layer disposed on at least one surface of the positive electrode collector, wherein the positive electrode active material layer comprises the aforementioned positive electrode material.
[0076] The positive electrode current collector may be aluminum foil or nickel foil, or any composite current collector disclosed in the prior art, such as but not limited to a current collector formed by combining the aforementioned conductive foil and a polymer substrate.
[0077] The present application also provides a secondary battery (such as a lithium-ion battery, a sodium-ion battery, etc.), including a housing, an electrode assembly and an electrolyte / electrolyte. The electrode assembly and the electrolyte / electrolyte are both located in the housing. The electrode assembly includes a separator, a negative electrode sheet and the positive electrode sheet, and the separator is disposed between the positive electrode sheet and the negative electrode sheet.
[0078] In some embodiments, the outer shell may be a packaging bag encapsulated by an encapsulation film (such as an aluminum-plastic film), such as a soft-pack battery. In other embodiments, the secondary battery may also be a steel-shell battery, an aluminum-shell battery, or the like.
[0079] In some embodiments, the electrode assembly may be a laminated structure, which is formed by alternately stacking a positive electrode sheet, a separator, and a negative electrode sheet. In other embodiments, the electrode assembly may also be a wound structure, which is formed by stacking a positive electrode sheet, a separator, and a negative electrode sheet in sequence and then winding them.
[0080] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector. The negative electrode current collector may use at least one of copper foil, nickel foil, stainless steel foil, titanium foil or carbon-based current collector, etc., or may be a composite current collector disclosed in any prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil and polymer substrate. The negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more. The battery provided in the embodiment of the present application has the advantages of high capacity, high initial efficiency, long cycle life, excellent rate performance and low expansion. The battery can be a lithium-ion battery, a sodium-ion battery, a solid electrolyte battery, etc., without limitation herein.
[0081] like Figure 1 and Figure 2 As shown in the figure, they are schematic diagrams of lithium removal and lithium insertion during the charging and discharging process of a lithium-ion battery prepared by using the positive electrode material provided in the embodiment of the present application. Figure 1 As shown in , when a lithium-ion battery is charged, lithium ions are released from the positive electrode and embedded in the negative electrode; Figure 2 As shown, when a lithium-ion battery is discharged, lithium ions are released from the negative electrode and embedded back into the positive electrode.
[0082] The embodiment of the present application prepares a secondary battery by using the aforementioned positive electrode material, and controls the aspect ratio X / Y of the particles in the positive electrode material to satisfy: 1≤X / Y≤1.6. After compaction under a pressure of 6T, the volume of particles below 1μm in the positive electrode material accounts for 2% to 4%, which can improve the long-term cycle performance, high-temperature storage performance and gas production performance of the battery while ensuring that the battery has good capacity and achieves an improvement in comprehensive performance. Among them, the aforementioned positive electrode material is used in a button cell, and the cycle performance of the battery is evaluated, and the cycle retention rate of 50 cycles at room temperature is ≥93%.
[0083] The scheme of the present application will be explained below in conjunction with the embodiments. Those skilled in the art will understand that the following examples are only used to explain the present application and cannot be construed as limiting the present application. Unless otherwise stated, the reagents, software and instruments not specifically stated in the following embodiments are all conventional commercial products or open source.
[0084] Embodiment 1: Step S1, weighing a compound having a chemical formula of Ni 0.6 Co 0.1 Mn 0.3 (OH) 2 2.5 kg of precursor, add 1.25 kg LiOH·H 2 O, 3000ppm ZrO 2 , 1000ppm Al 2 O 3 and 1000ppm Sr(OH) 2 The mixture was mixed in a high-speed mixer for 40 minutes to obtain a mixture.
[0085] Step S2, sintering the above mixture in an oxygen or air atmosphere at a furnace pressure of 50 Pa and a temperature of T1 = 700° C. for 6 hours to obtain a pre-sintered product.
[0086] Step S3, sinter the pre-sintered product in an oxygen or air atmosphere with a furnace pressure requirement of 50Pa, temperature T2: 960°C for 4h, the heating rate of the T2 stage is 3°C / min, temperature T3: 940°C for 6h; temperature T4: 920°C for 4h, to obtain a positive electrode material matrix.
[0087] Step S4, the obtained positive electrode material matrix is crushed, and the particle aspect ratio of the crushed positive electrode material matrix is measured under an electron microscope at a magnification of 3K. When the aspect ratio of the matrix satisfies 1≤X / Y≤1.6 and at the same time satisfies, after compaction under a pressure of 6T, the volume proportion of micropowders below 1μm in the matrix is calculated by a Malvern 3000 particle size tester to be in the range of 2% to 4%; the positive electrode material matrix is then continued to be processed subsequently.
[0088] Step S5, mixing the positive electrode material matrix that meets the requirements after crushing with 2000ppm WO 3 and 1000ppm TiO 2 Mix and put the mixture into a sagger, and sinter it at 600°C for 8h in an oxygen atmosphere with a heating rate of 3°C / min to obtain a positive electrode material.
[0089] Example 2 The difference from Example 1 is that in step S1, the general formula of the precursor is Ni 0.5 Co 0.2 Mn0.3 (OH) 2 The other steps are basically the same as those in Example 1, please refer to Example 1.
[0090] Example 3 The difference from Example 1 is that in step S1, the general formula of the precursor is Ni 0.7 Co 0.1 Mn 0.2 (OH) 2 The other steps are basically the same as those in Example 1, please refer to Example 1.
[0091] Example 4 The difference from Example 1 is that in step S2, the mixture is sintered for 8 hours in an oxygen or air atmosphere at a furnace pressure of 50 Pa and a temperature of T1 = 700° C. to obtain a pre-sintered product. The other steps are basically the same as Example 1, please refer to Example 1.
[0092] Example 5 The difference from Example 1 is that in step S1, a compound having a chemical formula of Ni 0.6 Co 0.1 Mn 0.3 (OH) 2 2.5 kg of precursor, add 1.25 kg of lithium salt (LiOH·H 2 O), adding 3000ppm ZrO 2 , 1000ppm Al 2 O 3 , 1000ppm Sr(OH) 2 and 500ppm WO 3 ; Mix in a high mixer for 40 min to obtain a mixture.
[0093] In step S2, the mixture is sintered in an oxygen or air atmosphere at a furnace pressure of 50 Pa and a temperature of T1 = 700° C. for 2 h to obtain a pre-sintered product.
[0094] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0095] Example 6 The difference from Example 1 is that in step S3, the pre-sintered product is sintered in an oxygen or air atmosphere with a furnace pressure of 50 Pa, at temperature T2: 960°C for 6 hours, at temperature T3: 940°C for 6 hours, and at temperature T4: 920°C for 4 hours to obtain a positive electrode material matrix.
[0096] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0097] Example 7 The difference from Example 1 is that in step S3, the pre-sintered product is sintered in an oxygen or air atmosphere at a furnace pressure of 50 Pa, at a temperature T2: 960°C for 2 hours, at a temperature T3: 940°C for 6 hours, and at a temperature T4: 920°C for 4 hours to obtain a positive electrode material matrix. The other steps are basically the same as in Example 1, please refer to Example 1.
[0098] Example 8 The difference from Example 1 is that in step S3, the pre-sintered product is sintered in an oxygen or air atmosphere with a furnace pressure of 50 Pa, at temperature T2: 980°C for 2 h, at temperature T3: 940°C for 8 h, and at temperature T4: 900°C for 4 h to obtain a positive electrode material matrix.
[0099] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0100] Example 9 The difference from Example 1 is that in step S3, the pre-sintered product is sintered in an oxygen or air atmosphere with a furnace pressure of 50 Pa, at temperature T2: 980°C for 2 h, at temperature T3: 950°C for 8 h, and at temperature T4: 920°C for 4 h to obtain a positive electrode material matrix.
[0101] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0102] Example 10 The difference from Example 1 is that in step S1, the lithium salt is anhydrous lithium hydroxide (LiOH).
[0103] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0104] Embodiment 11 The difference from Example 1 is that in step S1, 3% by mass of the precursor lithium peroxide is additionally added to the mixture as a pore-forming agent.
[0105] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0106] Example 12 The difference from Example 1 is that in step S3, the pre-sintered product is sintered in an oxygen or air atmosphere with a furnace pressure of 50 Pa, at temperature T2: 970°C for 2 h, at temperature T3: 950°C for 8 h, and at temperature T4: 930°C for 4 h to obtain a positive electrode material matrix.
[0107] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0108] Embodiment 13 The difference from Example 1 is that in step S1, a compound having a chemical formula of Ni 0.6 Co 0.1 Mn 0.3 O 2 Precursor 2.5 kg, LiOH·H 2 O, 1.25kg, add 3000ppm ZrO 2 , 1000ppm Al 2 O 3 and 1000ppm Sr(OH) 2 The mixture was mixed in a high-speed mixer for 40 minutes to obtain a mixture.
[0109] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0110] Embodiment 14 The difference from Example 1 is that in step S1, a compound having a chemical formula of Ni 0.6 Co 0.1 Al 0.3 (OH) 2 Precursor 2.5 kg, LiOH·H 2 O, 1.25kg, add 3000ppm ZrO 2 , 1000ppm Al 2 O 3 and 1000ppm Sr(OH) 2 The mixture was mixed in a high-speed mixer for 40 minutes to obtain a mixture.
[0111] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0112] Comparative Example 1 The difference from Example 1 is that in step S3, the sintering time T2 is 2 hours, the heating rate is 3° C. / min, and the sintering time T3 is 4 hours.
[0113] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0114] Comparative Example 2 The difference from Example 1 is that in step S3, the sintering time T2 is 6 hours, the heating rate is 6° C. / min, and the sintering time T3 is 8 hours.
[0115] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0116] Comparative Example 3 The difference from Example 1 is that in step S3, only one high-temperature sintering step is performed, the T2 sintering time is 12 h, the heating rate is 3° C. / min, and the subsequent T3 and T4 low-temperature sintering steps are not performed.
[0117] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0118] Comparative Example 4 The difference from Example 1 is that in step S3, only one high-temperature sintering step is performed, the sintering temperature T2 is 960°C, the sintering time T2 is 8h, the heating rate is 3°C / min, and the subsequent low-temperature sintering of T3 and T4 is not performed.
[0119] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0120] Comparative Example 5 The difference from Example 1 is that in step S3, the pre-sintered product is sintered in an oxygen or air atmosphere with a furnace pressure of 50 Pa, at temperature T2: 960°C for 2 h, at temperature T3: 900°C for 8 h, and at temperature T4: 850°C for 2 h to obtain a positive electrode material matrix.
[0121] The other steps are basically the same as those in Example 1, please refer to Example 1. The pre-sintered product is sintered in an oxygen or air atmosphere at a furnace pressure of 50 Pa, at a temperature T2: 960°C for 4 hours, a heating rate of 3°C / min in the T2 stage, at a temperature T3: 940°C for 6 hours; and at a temperature T4: 920°C for 4 hours to obtain a positive electrode material matrix.
[0122] Comparative Example 6 The difference from Example 1 is that in step S3, only one high-temperature sintering step is performed, the sintering temperature T2 is 970°C, the sintering time T2 is 12h, the heating rate is 3°C / min, and the subsequent low-temperature sintering T3 and T4 is not performed.
[0123] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0124] The following method was used to perform performance tests on the positive electrode materials obtained in the above Examples 1-14 and Comparative Examples 1-6.
[0125] 1. Aspect ratio test: Sample preparation: Take the crushed positive electrode material matrix, use a conductive adhesive with a length of 0.5 mm to pick up the material. After the material is taken, use an ear-cleaning bulb to blow the conductive adhesive surface with the material 10 times.
[0126] Electron microscope photography: A scanning electron microscope (SEM) was used to conduct the test under the electron beam condition of 5kV / 10mA. The screen with more particles was selected, and at least 10 electron microscope photos were taken at a magnification of 3K.
[0127] Aspect ratio test: Use software to measure the length M of the longest straight side of n particles randomly selected from each electron microscope photo, as well as the length N of the straight side perpendicular to the midpoint of the longest straight side. The average aspect ratio of the n particles is M / N, where n ≥ 50.
[0128] 2. Micro powder quantity test: Sample preparation: Place the crushed positive electrode material matrix into a mold and press it for 10 minutes using a pressure of 6 tons. After the pressing is completed, take the matrix out of the mold and grind the blocks with an agate mortar for 1 minute to disperse the blocks.
[0129] Measurement: The ground material is tested for particle size using a Malvern 3000 laser particle size analyzer to read the percentage of accumulated particles below 1 μm and the percentage of accumulated particles below 2 μm.
[0130] 3. Powder compaction density test: Using the American Carver 4350 tester, 1g of powder sample was weighed and placed in a mold and pressed with a pressure of 3T for 30s. After pressing, the height was tested and the compaction density was calculated.
[0131] 4. Specific surface area test: The specific surface area of the material is tested using the Microbeam 3020 nitrogen adsorption method.
[0132] Finished product pretreatment: weigh the mass of the empty sample tube m1; take 3g of sample, vacuum degas at 300℃ for 1h, and weigh the mass of the sample tube m2 after cooling; sample mass m=m2-m1.
[0133] Sample testing: The sample tube is placed in liquid nitrogen, and the nitrogen adsorption capacity V of the sample is measured at a series of relative pressures P / P0 to obtain the adsorption isotherm.
[0134] The isothermal adsorption curve was fitted, and the monolayer saturated adsorption capacity Vm was calculated according to the slope and intercept; then the specific surface area was calculated based on Vm.
[0135] 5. Tap density test: The American Quantachrome tap density tester DAT-4-220 was used.
[0136] The test steps include: clean the measuring cylinder, and then weigh the mass of the measuring cylinder as m1; add the sample to the measuring cylinder, try to make the sample surface level, and wipe the surrounding area with a paper towel; weigh the total mass of the sample and the measuring cylinder as m2; place the measuring cylinder on the vibration table and fix it with three symmetrical fixed feet; turn on the instrument, turn on the vibration switch, and the instrument will automatically stop after vibrating for a specified number of times; take out the measuring cylinder and read the volume of the sample. If the sample surface is horizontal after vibration, read the volume directly; if it is in a diagonal state, take the average value V of the readings at the highest and lowest points.
[0137] Calculation formula: tap density = (m2-m1) / V.
[0138] 6. pH test: Using Mettler FE28, take 5g of positive electrode material sample, add appropriate amount of pure water, ultrasonicate for 10 minutes, take it out and let it stand for 15 minutes. After the pH meter is calibrated, the composite electrode is inserted into the upper clear liquid to be measured. The pH value of the solution is calculated based on the potential difference between the measuring electrode and the reference electrode.
[0139] 7. Battery production and performance testing: a. Preparation of electrochemical performance test samples: Button cell production: Ingredients: NCM: SP: 5% PVDF glue = 93: 5: 2, high-speed stirring to disperse evenly; coating and drying: evenly coat the slurry on the aluminum foil, and put the electrode into a 100℃ forced air drying oven for 1.5h; rolling, punching and drying: when rolling, adjust the roller gap of the roller machine to 1mm, and roll 3 times; use a punching machine to punch holes, weigh, and put it in a vacuum drying oven to vacuum dry at 85℃ for more than 8h; button cell assembly: positive electrode shell-electrolyte-positive electrode sheet-electrolyte-diaphragm-electrolyte-lithium sheet-foam nickel-negative electrode shell (dried at 50℃), seal the battery after assembly, and take it out of the glove box for testing.
[0140] b. Power-off test: Capacity test: Place the battery at 3.0~4.4V, charge and discharge at 0.1C, and test the capacity in the first week.
[0141] Cycle test: The battery was placed in a constant temperature box at 25°C at 3.0~4.4V and charged and discharged at a rate of 0.5C / 1C for 50 times to obtain the cycle performance data.
[0142] The corresponding test results of the positive electrode materials of Examples 1-14 and Comparative Examples 1-6 are shown in Tables 1 and 2 below.
[0143] Table 1 Table 2 Examples 1-3 adjusted the Ni content in the precursor. For ternary positive electrode materials with different nickel contents, the preparation method of the embodiments of the present application was adopted to ensure that the aspect ratio of the single crystal particles in the positive electrode material is in the range of 1 to 1.6 (specifically 1.3), the particles are relatively round, and the proportion of micropowder is low (3%). The volume fraction of small particles of 0 to 1 μm to large particles of 0 to 2 μm is low (15%). The single crystal positive electrode material that meets the above conditions has good capacity and cycle performance.
[0144] Compared with Example 1, Example 4 further prolongs the pre-oxidation time, which is beneficial to the full embedding of lithium, reduces residual lithium and fine powder, and repairs the grain boundaries of the material, thereby further improving the roundness of the single crystal particles. The obtained single crystal particles have an aspect ratio of 1, which is more spherical.
[0145] Compared with Example 1, in Example 5, W is added to the first additive, and the pre-sintering time is shortened, the aspect ratio is increased, and the roundness is not as high as in Example 1, indicating that the length of the pre-sintering time affects the aspect ratio of the single crystal particles.
[0146] Compared with Example 1, Example 6 prolongs the time of the first stage sintering in step S3, increases the reaction time of particle fusion, and further reduces the micropowder content (to 2%).
[0147] Compared with Example 1, Example 7 shortens the first stage sintering time in step S3, shortens the reaction time of particle fusion, and increases the micro powder content (to 4%).
[0148] Compared with Example 1, Examples 8-9 adjusted the temperature and time of the secondary sintering, so as to control the content of the micropowder and the aspect ratio of the particles.
[0149] Compared with Example 1, Example 10 uses anhydrous lithium hydroxide (LiOH) and also uses the preparation method of the present application. The obtained positive electrode material can still meet the range of particle size and micro powder content.
[0150] Compared with Example 1, Example 11 can further allow oxygen to fully enter the interior of the precursor mixture by adding a pore-forming agent, so that the reaction can proceed fully, which is beneficial to improving the capacity and cycle performance of the positive electrode material.
[0151] Compared with Example 1, Example 12 increases the sintering temperature in step S3, shortens the high-temperature sintering time T2, and extends the low-temperature sintering time T3. The proportion of micropowders remains almost unchanged (3%), but the volume fraction of 0-1 μm particles to 0-2 μm particles decreases (to 6%), indicating that further fusion of the particles has occurred.
[0152] Compared with Example 1, the precursor of Example 14 is a nickel cobalt aluminum hydroxide precursor, and the preparation method of the present application is also used. The obtained positive electrode material can still meet the range of particle size and micropowder content, and has a higher capacity and excellent cycle performance.
[0153] It can be seen from Examples 1-14 of the present application that the prepared positive electrode materials all meet the requirement that the aspect ratio of the single crystal particles is 1 to 1.6, and at the same time, after compaction under a pressure of 6T, the volume proportion of micropowders below 1 μm in the matrix is calculated by the Malvern 3000 particle size tester to be in the range of 2% to 4%. The positive electrode materials that meet the above conditions all have high capacity and excellent cycle performance.
[0154] Compared with Example 1, Comparative Examples 1-3 adjusted the sintering stage, temperature and time of the secondary sintering. The aspect ratio of the single crystal particles in the prepared positive electrode material was relatively large (1.7), the micropowder content was high (at least 8%), and the capacity and cycle performance of the obtained positive electrode material were poor. Compared with Example 1, in Comparative Example 4, only high-temperature sintering was performed in the first sintering step, which shortened the time for particle fusion, the micropowder content was high (18%), the particle growth was insufficient, the aspect ratio was relatively small (1.2), and the cycle performance of the obtained positive electrode material was poor. Compared with Example 1, in Comparative Example 5, the gradient difference of the gradient sintering in the first sintering step was large, the high-temperature sintering time was short, and the low-temperature sintering temperature was low. At this time, the micropowder content was appropriate, but the aspect ratio of the particles was relatively large (1.7), the roundness of the particles was poor, the specific surface area was large, and the cycle performance of the obtained positive electrode material was poor. Compared with Example 1, in Comparative Example 6, only high-temperature sintering was performed in the first sintering step, and the high-temperature sintering temperature was relatively high, which promoted the fusion of particles. Although the aspect ratio of the particles was appropriate, the micropowder content was too low (1%), the compaction density of the material was low, and the capacity of the obtained positive electrode material was relatively low.
[0155] in addition, Figure 3 is a SEM photo of the positive electrode material of Example 1, from Figure 3 It can be seen that the aspect ratio of the single crystal particles in the positive electrode material of Example 1 is 1.3, the single crystal particles are round, and the amount of fine powder in the positive electrode material accounts for 3%. Figure 4 The SEM photo of the positive electrode material of Comparative Example 1 is shown in FIG. Figure 4 It can be seen that the aspect ratio of the single crystal particles of the positive electrode material of Comparative Example 1 is 1.7, the particles are not round enough, the specific surface area is large, and the amount of micropowder accounts for a large proportion (reaching 10%). Figure 5 It is a cycle comparison diagram of Example 1 and Comparative Example 1-2. Figure 5 It can be seen that the cycle performance of Comparative Example 1-2 is significantly worse than that of Example 1, which further proves that the positive electrode material prepared by the preparation method of the present application can meet the requirements of particle size and micropowder content, thereby effectively improving the capacity and cycle performance of the positive electrode material.
[0156] The above implementation modes are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the present application has been described in detail with reference to the above preferred implementation modes, a person skilled in the art should understand that the technical solutions of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application.
Claims
1. A positive electrode material, characterized in that: The average aspect ratio X / Y of the particles in the positive electrode material satisfies: 1≤X / Y≤1.6, wherein X is the length of the longest straight side of a single particle, and Y is the length of the straight side perpendicular to the midpoint of the longest straight side; after compaction under a pressure of 6T, the volume proportion of particles below 1 μm in the positive electrode material is 2%~4%.
2. The positive electrode material according to claim 1, characterized in that After compaction at a pressure of 6 T, particles with a size of 0 to 1 μm in the positive electrode material account for 10% to 20% of the volume fraction of particles with a size of 0 to 2 μm.
3. The positive electrode material according to claim 1, characterized in that The number of particles satisfying 1≤X / Y≤1.6 in the positive electrode material accounts for no less than 90%.
4. The positive electrode material according to claim 1, characterized in that The general formula of the positive electrode material is as follows: Li x Ni a Co b N c M d O2, N elements include at least one of Al and Mn, and M elements include at least one of Al, Ti, Zr, Mg, Sr, Ba, B, Ca, Nb, W, Sb, Ta, Sn and Y, wherein 0.98≤x≤1.1, 0.50≤a≤0.98, 0<b≤0.20, 0<c≤0.35, 0≤d≤0.10, a+b+c+d=1.
5. The positive electrode material according to claim 1, characterized in that The positive electrode material satisfies at least one of the following characteristics: (1) The positive electrode material is a single crystal positive electrode material, and the average particle size of the particles in the positive electrode material is 1 μm to 5 μm; (2) The median particle size D50 of the positive electrode material is 2 μm to 6 μm; (3) (D90-D10) / D50 of the positive electrode material ≤ 2; (4) The specific surface area of the positive electrode material is 0.4 m 2 / g ~0.8 m 2 / g; (5) The compaction density of the positive electrode material is ≥3.0g / cm 3 ; (6) The tap density of the positive electrode material is ≥1.5 g / cc; (7) The pH of the positive electrode material is ≤12.
6. A method for preparing a positive electrode material, characterized in that: The following steps are involved: Mixing a precursor with a first additive to form a mixture, and pre-sintering the mixture to obtain a pre-sintered product; Sintering the pre-sintered product once to obtain a positive electrode material matrix; The positive electrode material matrix is crushed, and the aspect ratio of the particles in the crushed positive electrode material matrix satisfies: 1≤X / Y≤1.6, wherein X is the length of the longest straight side of a single particle, and Y is the length of the straight side perpendicular to the midpoint of the longest straight side; after compaction under a pressure of 6T, the volume proportion of particles below 1 μm in the positive electrode material matrix is in the range of 2% to 4%; and The pulverized positive electrode material matrix is mixed with a second additive and subjected to secondary sintering to obtain the positive electrode material.
7. The method for preparing the positive electrode material according to claim 6, characterized in that: In the step of mixing the precursor and the first additive to form a mixture, the mixture further includes a pore former, and the amount of the pore former added accounts for 3% to 10% of the mass of the positive electrode material precursor; and / or The primary sintering includes a first sintering stage and N second sintering stages performed sequentially, wherein the temperature of each second sintering stage is lower than the temperature of the first sintering stage, and the temperature gradient of the N second sintering stages decreases, and N is an integer greater than or equal to 1.
8. The method for preparing the positive electrode material according to claim 7, characterized in that: The preparation method meets at least one of the following characteristics: (1) The pre-sintering temperature T1 is 500-900°C and the time is 2-8h; (2) The temperature T2 of the first sintering stage is 800-1000°C, and the time is 2-6 hours; the temperature of each second sintering stage is T2-n*ΔT, and the time is 2-6 hours, where n is the order of the second sintering stage in the N second sintering stages, n is an integer greater than or equal to 1, ΔT is 20-40°C, and the total time of the first sintering does not exceed 16 hours; (3) The positive electrode material precursor has the general formula of Ni a Co b N c (OH)2, wherein the N element is selected from at least one of Mn and Al, a+b+c=1, 0.50≤a≤0.98, 0<b≤0.20, 0≤c≤1-ab; (4) The first additive includes at least one of a lithium salt, a compound of Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn and Y, and the first additive contains at least a lithium salt; (5) The second additive includes at least one of compounds of B, Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn and Y.
9. A positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, characterized in that: The positive electrode active material layer includes the positive electrode material according to any one of claims 1 to 5 or the positive electrode material prepared by the method for preparing the positive electrode material according to any one of claims 6 to 8.
10. A secondary battery, characterized in that: The invention comprises a positive electrode material as claimed in any one of claims 1 to 5 or a positive electrode material prepared by the method for preparing a positive electrode material as claimed in any one of claims 6 to 8.
Citation Information
Patent Citations
Lithium ion ternary positive electrode material with high nickel content and low free lithium content, and preparation method and application thereof
CN109888207A
Positive electrode material for rechargeable lithium ion batteries
CN111615496A
Preparation method of high-performance lithium-rich single-crystal multi-element positive electrode material
CN112382738A
Positive electrode material, preparation method thereof and lithium ion battery
CN117913269A
Positive electrode material, electrochemical apparatus and electric device
WO2024036502A1
Cited By
Positive electrode material, positive electrode sheet, and secondary battery
WO2026138644A1